Real property in Australia : foundations and application - Hefferan, Michael J. (London : Routledge, 2021)
Real property in the form of investment, ownership and use pervades almost every aspect of daily lives andrepresents over 40% of Australia's wealth. Such assets do not exist in isolation - they are dynamic and forever evolving, impacted by a range of physical, economic, demographic, legal and other forces. Consequently, a true appreciation of individual assets and of the property sector as a whole demands an understanding of both the assets themselves and the context and markets in which they exist. The sector is complex and, on the face of it, confusing. It is however, not without logic and underlying themes and principles. This book provides a wider understanding of how the real property sector works. It covers topics such as the nature of real property and its functions, economic drivers, valuation principles, legal and tenure parameters, property taxation, land development and subdivision, asset and property management and sustainability - all critical components in this complexand critically importantsector. It provides a wide and balanced perspective for experienced practitioners, investors, students and anyone involved in property decision-making or wishing to secure a deeper understanding of these areas. The book integrates research-based theory with practical application and first-hand insights into a sector that underpins the Australian economy, its communities and its sustainability.
OCLC-licensed vendor bibliographic record.
Keywords: Real property -- Australia; BUSINESS & ECONOMICS / Real Estate; BUSINESS & ECONOMICS / Urban & Regional; ARCHITECTURE / Urban & Land Use Planning